2022
DOI: 10.3390/ph15070894
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anesthetic Efficacy of Rocuronium/Sugammadex in Otorhinolaryngologic Surgery: A Propensity Score-Matched Analysis

Abstract: The use of rocuronium/sugammadex in otorhinolaryngologic surgery improves intubation conditions and surgical rating scales. This study primarily aimed to evaluate the effect of the combination of rocuronium and sugammadex on intraoperative anesthetic consumption. The secondary outcomes were the intraoperative and postoperative morphine milligram equivalent (MME) consumption, duration of intraoperative hypertension, extubation time, incidence of delayed extubation and postoperative nausea and vomiting, pain sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Fourth, we did not compare the intraoperative consumption of volatile anesthetics between the two groups due to data unavailability. Wu et al recently showed that the use of rocuronium/sugammadex was associated with lower dosages of volatile anesthetics and opioids compared with cisatracurium/neostigmine [35]. Fifth, a small number of patients (4.1%) in the neostigmine group used cisatracurium in the original cohort.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Fourth, we did not compare the intraoperative consumption of volatile anesthetics between the two groups due to data unavailability. Wu et al recently showed that the use of rocuronium/sugammadex was associated with lower dosages of volatile anesthetics and opioids compared with cisatracurium/neostigmine [35]. Fifth, a small number of patients (4.1%) in the neostigmine group used cisatracurium in the original cohort.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This study aims to evaluate the frequency with which fistulectomy patients require a change from local to general or spinal anesthesia [14].…”
mentioning
confidence: 99%